Poetic Use of Syntaxical Figures in The Poetry of Azam Uktam and Minhojiddin Mirzo - Tumaris Butunbayeva (Zien Journals, 2021)
This article examines the linguistic bases used in the poetry of the famous Uzbek poets Azam Uktam and Minhojiddin Mirzo.
Keywords: Analogy; syntactic figures; trope; simile